Cytotoxic and genotoxic effects of nateglinide on human ovarian, prostate, and colon cancer cell lines (Annals of Medical Research, 2023)
Aim: Nateglinide, an oral anti-diabetic medication used to treat type 2 diabetes, activates ATP-dependent potassium channels in pancreatic beta cells and induces insulin secretion. Numerous antidiabetic medicines, particularly metformin, are known to drastically reduce the viability of cancer cells. This study examined the effects of nateglinide on the DNA and viability of human ovarian (A2780), prostate (LNCaP), and colon (Caco-2) cancer cells.Materials and Methods: Initially in the study, 1, 10, 100, and 1000 µM doses of nateglinide were administered for 24 hours to A2780, LNCaP, and Caco-2 cells. The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) test was used to measure cell viability. Using Graphpad Prism 8, the inhibitory logarithmic concentration values (LogIC50) of nateglinide in A2780, LNCaP, and Caco-2 cells were computed based on the results of the MTT experiment. These doses were applied to A2780, LNCaP, and Caco-2 cells for the Comet assay. The Bonferroni-corrected Mann–Whitney U test was used to compare groups, and a value of p
Keywords: Nateglinide; Ovarian cancer; Prostate cancer; Colon cancer